Validation and morphology of Begonia fagopyrofolia in B. sect. Stolonifera (Begoniaceae) in China - Chen, Wen-Hong; Wu, Jian-Yong; Radbouchoom, Sirilak; Shui, Yu-Min (Phytotaxa, 2021)
The invalid name, Begonia fagopyrofolia nom.nud., is validly published, with the addition of a description and illustration. As a member of Begonia sect. Stolonifera, it is similar to B. cehengensis, but differs in its climbing stem, obovate to suborbicular petals of the staminate and pistillate flowers, a 1.5–2.2 m long thin beak-like top of the fruit, and linear-lanceolate horns of the fruit. Our observations reveal that the new species differs from its most similar species (B. cehengensis) in the morphology of its leaf epidermis, seeds, pollen grains and placentation. The new species is designated as Vulnerable (VU) according to IUCN standards (2012).